Effects of light stroking massage with olive oil on acute pain severity and number of taken non-steroidal anti-inflammatory drugs among outpatients with extremities trauma: A double-blind, placebo-controlled superiority trial. (July 2022) - Nasiri, Morteza; Farsi, Zahra; Habibi, Hengameh; Fournier, Andrew; Rajai, Nahid
Abstract: Introduction: Currently, analgesics are used to alleviate acute pain after trauma; however, these drugs cause some undesirable adverse effects. Hence, there is a need for nonpharmacological methods to reduce trauma-induced pain. This study investigated the effects of massage with olive oil on acute pain severity and number of taken non-steroidal anti-inflammatory drugs (NSAIDs) among trauma patients. Methods: In this double-blind, placebo-controlled superiority trial, 42 outpatients who suffered from superficial injury in upper or lower extremities were randomly assigned to olive oil and placebo groups. Patients received a 5-min light stroking massage on the trauma site twice a day for nine consecutive days with 10 drops of either olive oil or placebo (liquid paraffin). Also, they received NSAIDs and applied cold and warm compresses on the trauma site. The pain severity (a 0–10 numerical pain rating scale) and the number of NSAIDs were recorded at four points of time, including before the intervention (baseline), and on the third, sixth, and ninth days of intervention. Results: There was a significant difference between the study groups in mean ranks of the number of NSAIDs taken on the baseline and third days ( P = 0.02, P = 0.009). Considering the number of NSAIDs taken during nine days as a covariate, a significant decrease in the pain severity was found in two groups during the nine days ( P time < 0.001). However, pain reduction over time was more significant in the olive oil group ( P time*group = 0.001). Also, mean changes in the pain severity compared to the baseline were significant on the sixth ( P = 0.001) and ninth ( P = 0.002) days of the intervention in favor of the olive oil group. Conclusion: Administration of light stroking massage with olive oil as a complementary method seems to be potentially effective in reducing the pain severity and use of NSAIDs among patients with trauma to the extremities.